2011
DOI: 10.1177/1088868311430825
|View full text |Cite
|
Sign up to set email alerts
|

Relative Deprivation

Abstract: Relative deprivation (RD) is the judgment that one is worse off compared to some standard accompanied by feelings of anger and resentment. Social scientists use RD to predict a wide range of significant outcome variables: collective action, individual achievement and deviance, intergroup attitudes, and physical and mental health. But the results are often weak and inconsistent. The authors draw on a theoretical and meta-analytic review (210 studies composing 293 independent samples, 421 tests, and 186,073 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
445
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 791 publications
(551 citation statements)
references
References 268 publications
19
445
3
2
Order By: Relevance
“…Therefore, people are likely to rely on heuristics in day to day life instead of more mentally taxing methods (Gigerenzer, Todd, & ABC Research Group, 1999). The idea that individuals use relative information to prescribe value is strongly supported by both theoretical predictions and empirical evidence (Festinger, 1954;Smith, Pettigrew, Pippin, & Bialosiewicz, 2012;Tversky & Kahneman, 1981,1986. Contextual factors, such as anchoring an evaluation on a reference point, seem to have predictable and robust effects on how people assess value (Kahneman & Tversky, 1979Shafir, Simonson, & Tversky, 1993;Thaler, 1985Thaler, , 1999).…”
Section: How Is It Being Assessed?mentioning
confidence: 82%
See 2 more Smart Citations
“…Therefore, people are likely to rely on heuristics in day to day life instead of more mentally taxing methods (Gigerenzer, Todd, & ABC Research Group, 1999). The idea that individuals use relative information to prescribe value is strongly supported by both theoretical predictions and empirical evidence (Festinger, 1954;Smith, Pettigrew, Pippin, & Bialosiewicz, 2012;Tversky & Kahneman, 1981,1986. Contextual factors, such as anchoring an evaluation on a reference point, seem to have predictable and robust effects on how people assess value (Kahneman & Tversky, 1979Shafir, Simonson, & Tversky, 1993;Thaler, 1985Thaler, , 1999).…”
Section: How Is It Being Assessed?mentioning
confidence: 82%
“…Emphasizing this point, the results from a meta-analysis of relative deprivation research indicate that the strength of the link between relative assessments and relevant outcome variables depends on whether the reference point used for the assessment is clearly specified by the researcher (Smith et al, 2012). Too often it seems, researchers studying relative deprivation do not clearly specify relative to what an individual feels deprived.…”
Section: How Is It Being Assessed?mentioning
confidence: 99%
See 1 more Smart Citation
“…60,61 If individuals perceive that their fellow in-group members are also experiencing the same kinds of unfair treatment, then it is easier for them to attribute the unfair treatment to discrimination rather than to their personal characteristics. Second, according to the relative deprivation theory, 62 subjective judgments that one is better off than others is associated with positive personal outcomes, 63 and people often engage in downward comparisons to maintain and/or boost their selfesteem and positive affect. [64][65][66] Given that Black Americans in the current sample perceived more discrimination happening to fellow in-group members than to themselves on average, reflected in a higher mean of perceived group-level discrimination than that of perceived personal-level discrimination (3.86 vs 3.18, respectively), this is suggestive of downward comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that individuals' subjective experience of disadvantage is a powerful predictor of actions aimed at confronting the disadvantage (Smith, Pettigrew, Pippin, & Bialosiewicz, 2012). At the societal level, perceiving the system as unfair increases the likelihood that individuals take part in protest (Jost et al, 2012;Rothmund, Becker, & Jost, 2016).…”
Section: Direct Participation In Political Actionmentioning
confidence: 99%